Acanthocephala from marine fish in the maritime border region of Indonesia and the Philippines - Dwi Pramardika Dhito; Satrija Fadjar; Sulistiono; Tiuria Risa; Budiman Nugraha Arifin (BIO Web of Conferences)
A total of 24 fish belonging to seven species were sampled from the waters of the Sangihe Islands in the border area of Indonesia and the Philippines. The fishes were examined to identify the genera of Acanthocephalan phylum parasites that infect marine fish, measure the prevalence and intensity of infection of these parasites, and analyze the correlation of biotic factors with Acanthocepala phylum parasite infection in marine fish. Two acanthocephalan genera (Echinorhynchus and Rhadinorhynchus) were found to infect the marine fish Aprion virescens (1/4) and Katsuwonus Pelamis (7/7). Aprion virescens had a strong correlation between biotic factors such as total length, fish weight and parasite infection, except for the fish condition factor, which had a weak correlation. In contrast, Katsuwonus pelamis fish had a strong correlation with weight and fish condition, whereas total length had a weak correlation with parasite infection. It can be concluded that marine fish at the border of Indonesia and the Philippines are infected with Echinorhynchus sp. with mild intensity, while Rhadinorhynchus sp. is infected with moderate intensity.